Development of microbial fuel cell using speek/cloisite 15A membrane for electricity generation from palm oil mill effluent [electronic resource] - Nur Dianaty Nordin, 1987- (2013)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2013